Meta-analysis of Lung Cancer Patients in COVID-19 - Ghouse Peer, Gajala Deethamvali; Pandey, Ramendra P. (Current Respiratory Medicine Reviews, 2023)
Background: Lung cancer patients have a higher chance of getting infected and showing severe outcomes from coronavirus disease 2019 (COVID-19). This infection influences the respiratory system, albeit other organs are also involved with high risk related to health. The blend of COVID-19 disease and lung cancer predicts a higher mortality rate and more serious clinical results. Objective: This research reports the Systematic Review and Meta-analysis correlation between COVID-19 patients with lung cancer and comprehensive proof with regards to the mortality of these patients. Methods: A systematic review and meta-analysis were planned to evaluate the data from a PubMed systematic search on Lung Cancer Patients reported by COVID-19, as well as an efficient literature review and information research from 2019 to 2021. Results: 22 out of 3639 review and research literature assessments were gathered, and 10951 patients were COVID +ve and suffering from cancer, with 21% of the patients suffering from SCLC and NSCLC, and lung cancer accounting for 6% of the mortality. Conclusion: Lung cancer patients who are suffering from COVID-19 additionally reflected the seriousness of the illness and higher rates of intensive care unit confirmations and mechanical ventilation. COVID-19 in patients with lung cancer is related to extreme disease and expanded mortality compared with patients with different tumours. There is conflicting proof of explicit lung cancer therapies' results. Until more conclusive data is available, lung cancer-coordinated therapy should be restarted as soon as possible in mild to moderate cases to avoid decline and cancer-related mortality.
Keywords: Non-small cell lung cancer (NSCLC)